Features of Dental Caries in Young Children: Epidemiology, Etiology, Prevention, Treatment - Jabbarova Zarnigor Bazarbayevna (Scientific Trends, 2024)
Caries in children is a special disease that has a complex multifactorial nature of multifaceted interaction. Assessment of the strength and degree of influence of risk factors for the development of the disease should be carried out in the specific condition of the patient, taking into account the stage of development and age-related structural features of the baby's teeth, as well as exogenous and endogenous conditions. Since some of the risk factors for caries are more or less related to objective conditions, attempts by "patients" or dentists to influence them are limited and can only be partially altered. However, large groups consist of risk factors that depend on the behavior of the child and his parents, and to minimize them both by the dentist and by self-help efforts.In this case, these factors are the main purpose of determining the scope and focus of treatment and preventive measures.
Keywords: Baby teeth, pediatric caries, risk factors, treatment and preventive measures.